Telaah Leksikal, Gramatikal, dan Kontekstual Terhadap Makna Kata Syahida pada QS. al-Baqarah ayat 185 - Budi Kisworo; H Hardivizon (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This writing contains a semantic study of surah Al-Baqarah verse 185.As it is known, fasting is explained by Allah SWT through surah Al-Baqarah verse 183-185.In the verse 183, Allah explains the obligation of fasting for the believers; the verse 184 contains an explanation of the days in which the obligation of fasting must be fulfilled; and the verse 185 implies the way to know the coming of the month of Ramadan as a month in which fasting is obligated.The mufassirins understand the verse 185 of Al-baqarah asinformation about the condition of someone who presents (meets) the month of Ramadan, then it is obligatory upon him to fast.This understanding departs from the word